Information and methods of prevention of unlawful behavior of minors (Zien Journal of Social Sciences and Humanities, 2022)
Measures and methods of prevention of unlawful behavior of minors, as well as problems of formation of a system of early prevention are considered. The author summarizes and analyzes international documents in this field, as well as the opinions of scientists on this topic, makes appropriate theoretical conclusions and proposals on the effectiveness and timeliness of prevention of offenses among minors. methods of preventive influence on juvenile offenders. The above provisions are of both scientific and practical importance